Paleoecological Significance of Complex Fossil Associations of the Eldonioid Pararotadiscus guizhouensis with other Faunal Members of the Kaili Biota (Stage 5, Cambrian, South China). (30th April 2018) - Zhao, Yuanlong; Wang, Mingkun; LoDuca, Steven T.; Yang, Xinglian; Yang, Yuning; Liu, Yujuan; Cheng, Xin
Abstract: The planktonic medusiform taxon Pararotadiscus guizhouensis (Zhao and Zhu, 1994) is one of the most abundant components of the Kaili Biota. Many specimens are in direct association with other taxa, including trilobites, brachiopods, hyolithids, echinoderms, and algae, as well as the trace fossil Gordia . Four types of interrelationships between P . guizhouensis and associated fossils are recognized: symbiosis, co-burial, attachment of benthic taxa on P . guizhouensis carcasses, and scavenging of P . guizhouensis carcasses. These associations of P . guizhouensis within the Kaili Biota are unique among occurrences of medusiform fossils in Burgess Shale-type biotas worldwide and provide important insights concerning ecological complexity in the Kaili Biota and in Cambrian marine communities in general.